Social activity and learning de-encapsulation under a multimodal approach in English Language Teaching - Santos, Carolina Favaretto; Ortenzi, Denise Ismenia Bossa Grassano (BELT - Brazilian English Language Teaching Journal, 2021)
In order to attempt to bring language learning practices closer to students’ daily lives, studies regarding Social Activity (Liberali, 2009), under the Social Historical Activity Theory (Engestrom, 1999) have been gaining space in current research (Larré, 2018; Silva, 2017; Zanella, 2017). Accordingly, as an emerging necessity from the context here described and from our society in general, environmental education became necessary, along with interdisciplinary practices, as stated in Brazil’s official curriculum guidelines. In addition, in the 21st century, with the advances of Information and Communication Technologies (ICT), the Pedagogy of Multiliteracies (Cope & Kalantzis, 2001) has become even more relevant in education, being it due to communication, social media, video, and images, for example. In light of this, the objective of this research paper is to analyze the outcome of an environmentally focused pedagogical intervention under a multimodal approach, developed during an internship program in a state school. After being in contact with planetary awareness in English language lessons, students customized ecobags alongside the Arts teacher, in an interdisciplinary way. Students’ productions were analyzed taking into account their multimodal choices when making meaning out of different semiotic modes, and to what extent learning de-encapsulation happened in this process. Results indicate that students were able to achieve synesthesia in their multimodal productions, combining linguistic, visual, spatial and gestural modes. Furthermore, learning de-encapsulation occurred as students made use of the environmental knowledge they acquired in English classes, not only by crossing boundaries inside the school, but also outside its walls.